Ultrasound-assisted bleaching of canola oil: Improve the bleaching process by central composite design - Icyer, Necattin Cihat; Durak, M. Zeki (ELSEVIER, 2018)
The goal of this study is to improve the bleaching process of canola oil by using ultrasound treatments under various parameters. The first of these parameters was the temperature (45 degrees C-75 degrees C)/ultrasonic power (20%-60%), the second was the amount of bleaching earth (0.1%-2% w/w), and the third was the contact time (2-15 min). The response surface central composite design was created and the bleaching parameters for canola oil were optimized based on the spectrophotometric analysis at 446 nm and responses to the lovibond color scales. The optimum conditions obtained by ultrasonic treatment of canola oil bleaching were compared with the conventional bleaching conditions. Especially, properties of bleached oil such as free fatty acids, peroxides, p-anisidine values, conjugated diens and triens, totox, fatty acid compositions and red-yellow colors have been evaluated. The results showed that integration of the ultrasonic treatment into the bleaching process, could possibly reduce the applied oil temperature by 25%, the contact time by 50%, and the color value by 6-34% compared to the conventional method.
Keywords: Bleaching; Ultrasound; Canola oil; Optimization; Response surface methodology; Central composite design; PARAMETERS; KINETICS; EARTHS; Food Science & Technology